An emerging role for epigenetic factors in relation to executive function. (20th November 2017) - Ibrahim, Omar; Sutherland, Heidi G; Haupt, Larisa M; Griffiths, Lyn R
Abstract: Background: Executive function (EF) includes a range of decision-making and higher-order thinking processes. Although the genetic basis of EF has been studied and reviewed, epigenetic factors that influence EF are an emerging field of interest; here, we summarize the current research. Methods: Work relating to different word combinations of 'Executive Function' and 'Epigenetic' was identified through three academic search directories. Inclusion criteria were human populations, EF testing, epigenetic testing or genotyping related to epigenetic regulation. Results: To date, 14 studies have been reported, which examined epigenetic variation, in particular DNA methylation, in relation to EF assessments conducted in human subjects, with some positive associations found. Study populations included healthy cohorts, as well as psychiatric and neurological patient cohorts. Conclusion: Epigenetics in relation to EF is an emerging area of investigation with relatively few studies to date. Most assay DNA methylation, with some studies suggesting that epigenetic factors can be associated with EF. EF constitutes complex phenotypic and genotypic correlates that differ because of cohort attributes as well as the targeted task examined. Larger studies are required to further elucidate the contribution of epigenetic factors to EF with the identification of epigenetic modifications influencing EF having potential to provide new biomarkers for neuropsychiatric disorders.